Cohesive Devices in English Contents Written by Blog Writers and English Department Students - Gullit T Taufan (Universitas Ahmad Dahlan, 2021)
This study was conducted to investigate the use of cohesive devices in English writings written by Indonesian blog writers and English department students. It also focused on investigating the appropriateness of the use of cohesive devices in the writings. The data were English texts written by 15 blog writers and 15 English department students and analyzed manually by employing content analysis. The findings show that (1) lexical cohesion was used most frequently by both groups of the study followed by reference, connectives, and substitution and (2) the blog writers were more capable in using the cohesive devices appropriately in their writings.